Paleoproteomic study of the Iceman’s brain tissue - Maixner, Frank; Overath, Thorsten; Linke, Dennis; Janko, Marek; Guerriero, Gea; van den Berg, Bart H. J.; Stade, Bjoern; Leidinger, Petra; Backes, Christina; Jaremek, Marta; Kneissl, Benny; Meder, Benjamin; et al. (Cellular and molecular life sciences, 2013)
The Tyrolean Iceman, a Copper-age ice mummy, is one of the best-studied human individuals. While the genome of the Iceman has largely been decoded, tissue-specific proteomes have not yet been investigated. We studied the proteome of two distinct brain samples using gel-based and liquid chromatography-mass spectrometry-based proteomics technologies together with a multiple-databases and -search algorithms-driven data-analysis approach. Thereby, we identified a total of 502 different proteins. Of these, 41 proteins are known to be highly abundant in brain tissue and 9 are even specifically expressed in the brain. Furthermore, we found 10 proteins related to blood and coagulation. An enrichment analysis revealed a significant accumulation of proteins related to stress response and wound healing. Together with atomic force microscope scans, indicating clustered blood cells, our data reopens former discussions about a possible injury of the Iceman’s head near the site where the tissue samples have been extracted.
Gesehen am 16.06.2021